Complete metabolic response in patients with advanced non-small cell lung cancer with prolonged response to immune checkpoint inhibitor therapy. Issue 3 (31st March 2021) - Ferdinandus, Justin; Metzenmacher, Martin; Kessler, Lukas; Umutlu, Lale; Aigner, Clemens; Kambartel, Karl-Otto; Grünwald, Viktor; Eberhardt, Wilfried Ernst Erich; Fendler, Wolfgang Peter; Herrmann, Ken; Faehling, Martin; Christoph, Daniel Christian
Abstract : Introduction: Immunotherapy is the new standard of care in advanced non-small cell lung cancer (NSCLC). Recently published data show that treatment discontinuation after 12 months of nivolumab treatment is associated with shorter survival. Therefore, the ideal duration of immunotherapy remains unclear, and finding markers of beneficial outcomes is of great importance. Here, we determine the proportion of complete metabolic responses (CMR) in patients who have not progressed after 24 months of immunotherapy. Methods: This is a retrospective analysis of 45 patients with positron emission tomography using 2-[18F]fluoro-2-deoxy-D-glucose imaging for assessment of residual metabolic activity after at least 24 months. CMR was defined as uptake in tumor lesions below background levels, using mediastinum as a reference. Results: Out of 45 patients, 29 patients had a CMR (64%). CMR was observed more frequently in non-first-line patients. Patients with CMR were younger (median 65.7 vs 75.5, p=0.03). Fourteen patients with CMR have discontinued therapy and have not progressed until time of analysis; however, median follow-up was only 5.6 (range 0.8–17.0) months. Conclusion: After a minimum of 24 months of palliative immunotherapy for NSCLC, CMR occurred in almost two thirds of patients. Potentially, achievement of CMR might identify patients, for whom palliative immunotherapy may be safely discontinued.